THE ROLE OF TEACHERS IN IMPLEMENTING DISCOVERY LEARNING MODEL LEARNING STRATEGIES IN ELEMENTARY SCHOOLS - Fadli, Muhammad (Edelweiss : Journal Of Innovation In Educational Research, 2025)
This study aims to analyze the role of teachers in the implementation of discovery learning model-based learning strategies at the elementary school level. This learning model emphasizes the active participation of students in discovering concepts and principles independently, with the assistance of teachers who act as facilitators, motivators, and learning managers. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation in several selected elementary schools. The findings of the study show that the effectiveness of the implementation of discovery learning is highly dependent on the capacity of teachers to create a conducive learning environment, manage the learning process efficiently, and provide appropriate reinforcement to students. These results emphasize the urgency of continuous training and the provision of adequate learning resources to improve teachers' competence so that the learning process runs optimally and is able to produce maximum learning outcomes.